KERJASAMA KPK DAN SFO DALAM KERANGKA UNCAC TERKAIT KASUS KORUPSI TRANSNASIONAL: Studi Kasus Suap Garuda Indonesia Periode 2017-2020 - Ubaity Rosyada, (2021)
The Garuda Indonesia bribery case is evidence of a transnational corruption case involving many countries. This case is a bribery case in the private sector where British Rolls Royce officials bribed Garuda Indonesia officials to secure the position of aircraft engine supplier for Garuda Indonesia. This thesis uses a descriptive qualitative research method that aims to describe how the cooperation between KPK and SFO in uncovering the Indonesian Garuda bribery case for the 2017-2020 period. The author uses the theory of liberal institutionalism, the concept of complex interdependence, and the concept of corruption in this study. This research will describe how the cooperation between KPK and SFO in uncovering this case. The KPK and SFO collaborate with the type of parallel investigation where two collaborations are used successively. First, investigations in each jurisdiction and exchange of information based on the MoU between the two institutions which were signed in 2010. Second, using the MLA mechanism to formalize evidence by sending an MLA application letter from the Indonesian Central Authority to the British Central Authority based on UNCAC and diplomatic relations because the two countries do not yet have a bilateral MLA agreement.